2015
DOI: 10.1093/mnras/stv745
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the Milky Way's bar outside the bulge

Abstract: While it is incontrovertible that the inner Galaxy contains a bar, its structure near the Galactic plane has remained uncertain, where extinction from intervening dust is greatest. We investigate here the Galactic bar outside the bulge, the long bar, using red clump giant (RCG) stars from UKIDSS, 2MASS, VVV, and GLIMPSE. We match and combine these surveys to investigate a wide area in latitude and longitude, |b| 9 • and |l| 40 • . We find: (i) The bar extends to l ∼ 25 • at |b| ∼ 5 • from the Galactic plane, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
368
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(407 citation statements)
references
References 80 publications
(144 reference statements)
37
368
2
Order By: Relevance
“…Most estimates agree on a bar orientation 2 of φ b = 30 • ± 10 and a pattern speed of Ω b /Ω 0 = 1.9 ± 0.1, where Ω 0 is the local standard of rest (LSR) rotation rate. A drastically different bar pattern speed has recently been suggested by the longer bar half-length measured by Wegg et al (2015), compared to previous works -r b = 5.0 ± 0.2 kpc, which places the CR 2 See Fig. 2, second panel, for the definition of the bar angle.…”
Section: The Milky Way Bar and Spiralsmentioning
confidence: 65%
“…Most estimates agree on a bar orientation 2 of φ b = 30 • ± 10 and a pattern speed of Ω b /Ω 0 = 1.9 ± 0.1, where Ω 0 is the local standard of rest (LSR) rotation rate. A drastically different bar pattern speed has recently been suggested by the longer bar half-length measured by Wegg et al (2015), compared to previous works -r b = 5.0 ± 0.2 kpc, which places the CR 2 See Fig. 2, second panel, for the definition of the bar angle.…”
Section: The Milky Way Bar and Spiralsmentioning
confidence: 65%
“…Figure 10 shows the stars on the model of the Galactic bulge of Li & Shen et al (2012), who identified an X-shaped component in the bar/boxy bulge models of Shen et al (2010) that matched the stellar observations of McWilliam & Zoccali (2010). The Shen et al (2010) model was, in turn, tailored to reproduce the kinematic data of the Bulge Radial Velocity Assay (Howard et al 2008; see also Wegg et al 2015, their Fig. 1).…”
Section: Spatial Distributionmentioning
confidence: 90%
“…Finding these metal-poor stars and ascertaining their membership with the bulge is not only of interest for the sake of reconstructing the chemical evolution of the bulge, but also has important implications for studying the morphology of the bulge. Number counts of the red clump, which led to the discoveries of, for instance, bar, boxy and X-shaped substructures (e.g., McWilliam & Zoccali 2010;Wegg et al 2015) employed certain cuts in colour-magnitude space. However, a prominent population of metal-poor, thus bluer, stars can be missed by fixed colour criteria, which could lead to biased, reconstructed spatial structures.…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly due to the fact that the bar has not grown quite as much as in the Milky Way. The bar in the model has a radius of ∼ 3 kpc , while the bar in the Milky Way extends to ∼ 4.5 − 5 kpc (Wegg et al 2015). The relatively high gas inflow rate to the centre of the model, with the attendant angular momentum transport and high star formation rate, is probably the source of this slow growth.…”
Section: Caveats About the Modelmentioning
confidence: 93%